Practical training applications for speed and agility development in soccer players; a mixed methods approach - Wing, C. (Journal of Australian Strength and Conditioning, 2017)
There is a growing focus within elite level Soccer upon speed and agility performance. The aim of this article is to provide practical training guidelines within these areas of focus for Strength and Conditioning coach`s working with Soccer athletes. Several different training modalities are explored using the current literature to support their inclusion. This paper recommends a mixed methods approach where gym based training consisting of maximal strength and power exercises should be programmed. Plyometric exercises should also be included with the aim of optimising GCT (ground contact time) and force production. Technical aspects of acceleration, top speed running, and change of direction should also be coached to ensure optimal running mechanics. These may be incorporated into team warm ups and progressed to reactive drills upon mastery. Finally, small sided games may be carefully manipulated in order to promote speed and agility training. This includes pitch size, team numbers and special rules. An example is provided. A coach`s tool box is included highlighting exercise recommendations for acceleration, top speed and agility performance and a weekly planner suggesting when these drills may be incorporated into a typical soccer training week.